2018
DOI: 10.1007/s11060-018-2862-0
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-related epilepsy: epidemiology, pathogenesis and management

Abstract: Surgical and medical treatments of tumor-related epilepsy remain challenging as additional factors such as the extent of surgical resection, interactions with tumor-related oncological treatments and anti-epileptic medication related side effects need to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
22

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 75 publications
1
74
0
22
Order By: Relevance
“…There is an inverse relationship between seizure prevalence and tumor growth rate, 4 and actually, in our case, although we were dealing with a highly aggressive tumor, the follow-up brain MRIs did not show a fast-growing rate, which could allow enough time for the tumor cells to re-organize, vascularize, and develop mechanisms necessary for epileptogenesis. 4 Under some pathophysiological conditions, operculo-insular lesions may produce location-specific painful epileptic seizures. Functional imaging studies have identified several cortical areas activated by painful stimuli, referred as "pain matrix," including, among others, the primary somatosensory area, the supplementary motor area, the insula, and the anterior frontal or the posterior parietal cortices.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…There is an inverse relationship between seizure prevalence and tumor growth rate, 4 and actually, in our case, although we were dealing with a highly aggressive tumor, the follow-up brain MRIs did not show a fast-growing rate, which could allow enough time for the tumor cells to re-organize, vascularize, and develop mechanisms necessary for epileptogenesis. 4 Under some pathophysiological conditions, operculo-insular lesions may produce location-specific painful epileptic seizures. Functional imaging studies have identified several cortical areas activated by painful stimuli, referred as "pain matrix," including, among others, the primary somatosensory area, the supplementary motor area, the insula, and the anterior frontal or the posterior parietal cortices.…”
Section: Discussionmentioning
confidence: 53%
“…5 Some cases of ictal pain with foci originating in the frontal, parietal, and temporal regions have been described with surface EEG. 4,6 However, data from functional cortical mapping by using direct cortical stimulation suggest that the origin of painful somatosensory seizures arises solely from the medial part of parietal operculum or the posterior and upper part of the insular cortex. 7,8 Taking into account the cortical mapping studies and the localization of our patient's glioblastoma, we suggest that the painful seizure has a left operculo-insular origin and that the rhythmic activity captured on the surface EEG represents propagation to the primary parietal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…(2) insufficient time for cells of high-grade tumors to reorganize, vascularize, and develop mechanisms necessary for epileptogenesis; and (3) slow-growing tumor cells may possess intrinsic epileptogenic properties. [6][7][8] As the propensity for malignant progression is very low in LEATs, seizure control may be the main treatment target. Unfortunately, there is a high incidence of drug-resistant seizures among LEAT patients; consequently, although LEATs account for only 2%-5% of all brain tumors and are the etiology of seizures in only 1%-3% of pediatric epilepsy patients, LEATs are the second-most common reason for epilepsy surgery in children.…”
Section: Introductionmentioning
confidence: 99%
“…A TC tem várias vantagens, as quais incluem menor custo, velocidade de digitalização, acessibilidade imediata e facilidade de uso, o que proporciona uma modalidade de imagem relativamente confiável para a maioria dos pacientes. Além disso, a tomografia computadorizada de última geração pode gerar imagens encefálicas em segundos (CHEN et al, 2018 (FISHER et al, 2014).…”
Section: Neuroimagemunclassified
“…A ILAE também recomenda que pacientes que tenham epilepsia refratária sejam submetidos a um estudo de ressonância magnética se a TC for normal. Atualmente, nos EUA, a ressonância magnética é considerada o padrão na avaliação de pacientes com epilepsia(CHEN et al, 2018).A ressonância magnética é o procedimento de imagem de escolha na investigação de pacientes com epilepsia. As vantagens da ressonância magnética em relação à TC são numerosas e não precisam de maior elaboração.…”
unclassified